P2X7 Receptor Activity Limits Accumulation of T Cells within Tumors - Romagnani, Andrea; Rottoli, Elsa; Mazza, Emilia Maria Cristina; Rezzonico-Jost, Tanja; De Ponte Conti, Benedetta; Proietti, Michele; Perotti, Michela; Civanelli, Elisa; Perruzza, Lisa; Catapano, Alberico L.; Baragetti, Andrea; Tenedini, Elena; et al. (Cancer research (Chicago, Ill.), 2020)
Extracellular ATP (eATP) is a signaling molecule that variably affects all cells of the immune system either directly or after hydrolysis to adenosine. Although eATP is virtually absent in the interstitium of normal tissues, it can be present in the hundreds of micromolar range in tumors, a concentration compatible with activation of the ATP-gated ionotropic P2X7 receptor. Here, we show that P2X7 activity in tumor-infiltrating lymphocytes (TIL) induces cellular senescence and limits tumor suppression. P2X7 stimulation affected cell cycling of effector T cells and resulted in generation of mitochondrial reactive oxygen species and p38 MAPK-dependent upregulation of cyclin-dependent kinase inhibitor 1A (Cdkn1a, encoding for p21Waf1/Cip1). Lack of P2X7 promoted a transcriptional signature that correlated with enhanced cytotoxic T-cell response in human solid tumors. In mice, transfer of tumor-specific T cells with deletion of P2rx7 significantly reduced tumor growth and extended survival. Collectively, these findings uncover a purinergic checkpoint that can be targeted to improve the efficacy of cancer immunotherapy strategies.